2009
DOI: 10.1007/s00234-009-0635-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo hemodynamic analysis of intracranial aneurysms obtained by magnetic resonance fluid dynamics (MRFD) based on time-resolved three-dimensional phase-contrast MRI

Abstract: Each intracranial aneurysm in this study had at least one spiral flow. The WSS was lower and OSI was higher at the apex of the spiral flow than the whole aneurysmal wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…Although OSI was significant throughout the LV, the apex recorded significantly higher 3D and axial OSI than the base and midV (Table 1). High OSI in arteries is frequently associated with vascular pathologies 20, 21…”
Section: Resultsmentioning
confidence: 99%
“…Although OSI was significant throughout the LV, the apex recorded significantly higher 3D and axial OSI than the base and midV (Table 1). High OSI in arteries is frequently associated with vascular pathologies 20, 21…”
Section: Resultsmentioning
confidence: 99%
“…These are well summarized by Singh et al 42 Two hemodynamic indices, wall shear stress (WSS) and oscillatory shear index (OSI), have received particular attention due to their influence on endothelial cell behavior. 6,40 Although studies from Rayz et al, 36 Boussel et al, 1 and Isoda et al 22 showed that in vivo measurement of these quantities is possible using magnetic resonance, inherent limitations in the current technology impede its use, especially for smaller aneurysms, in large cohort studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the WSS can serve not only as a marker for increased stress and thus a vessel wall location that is particularly at risk but also as a disease course parameter in known vessel pathology [12,13]. A relationship between WSS and the occurrence/rupture of intracranial aneurysms is presumed [14,15].…”
Section: Wall Shear Stress (Wss)mentioning
confidence: 99%